Decomposing fecundity and evaluating demographic influence of multiple broods in a migratory bird. Issue 5 (21st February 2021) - Tenan, Simone; Becker, Detlef; Tolkmitt, Dirk; Schaub, Michael
Abstract: Relevance of breeding season fecundity as a driver of population dynamics has been highlighted by many studies. Despite that, knowledge about how brood type specific (i.e. first, second or replacement) fecundity affects demography of multiple‐brooded species is limited. In fact, estimation of brood type specific fecundity is often challenging due to imperfect detection of nesting attempts. We examined the demographic contribution and the feedback on population density of different components of fecundity, along with other vital rates, in a facultative multiple‐brooded migratory bird. We used a novel formulation of a fecundity model that allows incorporating reproductive data for which information on the type of brood was unknown in some cases, and embedded it into an integrated population model (IPM) to obtain consensual estimates of all demographic rates, including brood type specific fecundities, reproductive success probabilities and proportion of breeding pairs that performed a second or replacement brood. We then conducted transient life table response experiments on IPM estimates to account for non‐stationary environments. We applied the model to two 20‐year datasets collected in a Swiss and a German local population of wrynecks Jynx torquilla . Brood type specific fecundities and temporal patterns of brood type specific probabilities of success, number of successful and unsuccessful first broods, probability of starting a second or a replacement brood and proportion of pairs that performed a second or a replacement brood differed between the two populations. However, changes in immigration rate and apparent survival were the dominant contributors to temporal variation and large sequential changes in realized population growth rates in both populations. In the Swiss population we also found that second brood fecundity declined when population size increased. Our study provides insight into the reproductive processes that affect population dynamics and mediate density‐dependent fecundity in a migratory bird. In addition, the analytical approach proposed can be used in other studies of multiple‐brooded species to maximize the use of available fecundity data through the estimation of unknown brood types, thus favouring a better understanding of the demographic contribution of brood type specific fecundity. Abstract : A novel analytical approach for the study of fecundity components of multiple‐brooded species and maximize the use of available fecundity data through the estimation of unknown brood types, favouring a better understanding of the demographic contribution of brood type specific fecundity while accounting for non‐stationary environments.